"It’s a Jungle Out There:" Blackness and Disability in Monk - Pickens, Ther (Disability Studies Quarterly, 2013)
In Monk, the social structures that create disability have a relationship of reciprocal maintenance with the structures that sustain race. Specifically, I examine the moments in which Adrian’s disability and other characters’ blackness creates tension. These scenes are typically understood as humorous, drawing on Adrian’s disability and stock figures like the angry black man, Mammy, and the murderous hip-hop star. Yet, the commitment to these narratives remains tenuous because the tension between Adrian and the black characters is not always contentious, nor is it a consistently missed opportunity for nuance. Instead, I argue Monk reveals a more complex interplay between narratives of blackness, disability, and white liberalism. Namely, Adrian’s awkward exchanges lay bare the tensions present and open up space to see that we read disabled and racial identities in contact according to a logic determined not just by ability, but also by race.